Penerapan nilai-nilai pancasila terhadap kekerasan dalam rumah tangga - Aisyah, Siti - (Maliki Interdisciplinary Journal, 2025)
This research was conducted to identify the application of Pancasila values as an effort to prevent domestic violence (KDRT) in Indonesian society. The rising number of domestic violence cases, which can damage Pancasila values and violate human rights, is the background for this study. A qualitative approach was used in this research by collecting data from existing journals and employing descriptive data analysis methods. The findings show that the large number of domestic violence cases requires significant efforts, one of which is the application of Pancasila values in daily life. Pancasila, with its five principles containing noble values, plays an important role in shaping a society that respects each other and upholds social justice. Therefore, the application of Pancasila values can be an effective preventive measure to reduce domestic violence and protect human rights. In conclusion, Pancasila values are essential in preventing domestic violence and serve as a reference for establishing fair laws that can protect every family member in Indonesia.